Participation in a clinical trial for a child with cancer is burdensome for a minority of children. (27th April 2016) - van der Geest, Ivana M.M.; van den Heuvel‐Eibrink, Marry M.; Zwaan, C. Michel; Pieters, Rob; Passchier, Jan; Darlington, Anne‐Sophie E.
Abstract: Aim: This study explored how parents who had lost a child to cancer felt about them taking part in a clinical trial. Methods: A retrospective questionnaire was sent to parents who had lost a child to cancer. They were asked whether their child took part in a clinical trial during their palliative phase, their motives for their child's participation, how they perceived their child's burden and whether they would, hypothetically speaking, enrol again. Results: The 24 parents of 16 deceased children who had participated in a clinical trial explained their motives for their child's participation. The most common answers, with multiple responses, were treatment for future patients (n = 16), hope for a cure (n = 9) and prolonging their child's life (n = 6). Eight parents said that participating was not burdensome for their child and four said it was very burdensome, with others answering in between. None of the parents would decline participation if they would be in the same situation again. Conclusion: Performing clinical trials, even in a vulnerable population, such as children with cancer at the end of life, may not always lead to increased burden. None of the parents would in future, given the same circumstances, decline participation in a clinical trial. Abstract :